Pelatihan Edukatif: Strategi Meningkatkan Konsentrasi Belajar Anak melalui Lima Metode Sederhana dan Menyenangkan - Muhamad Safa’udin; Ratna Isnawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase the learning concentration of SD Negeri Pojok Kediri students through educational training with five simple and fun methods, namely focus games, Pomodoro Kids techniques, light physical activity, mindfulness exercises, and relaxation. The main problem faced by schools is the low level of focus of students during learning, especially when the material requires high concentration and sustained attention duration. The method of the activity includes initial observation to identify classroom conditions, teacher training related to the application of methods, direct application in the classroom, and periodic mentoring and evaluation. The results showed a significant improvement in students' focus skills, which was characterized by increased attention duration, faster response to instructions, and more active student involvement in the learning process. Teachers also reported that the classroom atmosphere became more conducive, orderly, and interactive after the methods were applied consistently. In addition, positive behavioral changes such as self-regulation skills, better emotion management, and more regular learning habits appear. Thus, this training has proven to be effective, easy to implement, and has the potential to be used as a sustainable strategy to improve the quality of the teaching and learning process in elementary schools.